2016
DOI: 10.1515/agr-2016-0013
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Regeneration Potential of Extinct Plants Starting From Old Seeds, by in Vitro Technology

Abstract: The aim of the study is to try a systematic and rational exploration of regeneration potential of extinct taxons, starting from old seeds found in the soil or in the herbarium, to study their germination potential with the purpose of biodiversity conservation. The species involved in this study are: Achillea spinosa, Chenopodium wolfii. Several protocols for the in vitro propagation of the species, starting from the seed are described in this study. The presence of callus during micropropagation of plants has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…In recent years, a few studies investigated the use of herbaria for recovering extirpated populations or even extinct species from seeds preserved in herbarium specimens (Nakahama & al., 2015; Abeli & al., 2020; Albani Rocchetti & al., 2022a), and several studies have shown that old seeds stored under suboptimal conditions in herbarium specimens can germinate (Magrini & al., 2010; Godefroid & al., 2011; Molnár & al., 2015; Cosac & al., 2016; Wolkis & al., 2022). Generally, germination of seed from seed banks should be preferred, as the material is stored under optimal conditions to maintain seed viability over time, so herbaria may be useful in exceptional cases, e.g., if no seeds from seed banks are available (e.g., Vincetoxicum pycnostelma Kitag.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few studies investigated the use of herbaria for recovering extirpated populations or even extinct species from seeds preserved in herbarium specimens (Nakahama & al., 2015; Abeli & al., 2020; Albani Rocchetti & al., 2022a), and several studies have shown that old seeds stored under suboptimal conditions in herbarium specimens can germinate (Magrini & al., 2010; Godefroid & al., 2011; Molnár & al., 2015; Cosac & al., 2016; Wolkis & al., 2022). Generally, germination of seed from seed banks should be preferred, as the material is stored under optimal conditions to maintain seed viability over time, so herbaria may be useful in exceptional cases, e.g., if no seeds from seed banks are available (e.g., Vincetoxicum pycnostelma Kitag.…”
Section: Introductionmentioning
confidence: 99%